Implementation of unified power quality conditioner (UPQC) based on current source converters for distribution grid and performance monitoring through LabVIEW Simulation Interface Toolkit server: a cyber physical model - Senthilnathan, Karthikrajan; Annapoorani, Iyswarya (IET generation, transmission & distribution, 2016)
This study describes a new configuration of unified power quality conditioner (UPQC) based on current source converters (CSC) topology with left shunt configuration. It consists of photo voltaic (PV) source and ultra-capacitor with a buck–boost converter which is utilised for maintaining the constant DC-link current. The compensation of sag, swell, unbalance, fault conditions is done by proposed UPQC-CSC model. The control algorithm for UPQC is based on synchronous reference frame theory and hysteresis loop for the pulse generation. The performance analysis of the proposed work is done by interfacing the SIT server of host computer to LabVIEW and MATLAB/Simulink using transmission control protocol/Internet protocol communication network. Results proved that the proposed system is able to compensate voltage at sag, swell, unbalance and fault conditions in distribution network.